ANALISIS PENGGUNAAN AUTOMATIC METER READING (AMR) PADA SCADA KONTROL BAGI PELAYANAN KONSUMEN - Sugeng, Sugeng (JREC (Journal of Electrical and Electronics), 2015)
SCADA (Supervisory Control And Data Acquisition) which a meaning and purpose of a dataacquisition of the process system is collected and processed into information required by theoperator, controlling a system of processes in an integrated and centralized. Control of electric powernetwork based SCADA systems is absolutely necessary because the growth of electricity is very high.This adds to the more complex network system of electric power in order to reach a good and reliableelectricity supply in adequate quantity and quality. Automatic Meter Reading (AMR) is one of theequipment in the SCADA control which is monitor and perform data retrieval and transmission ofelectrical energy usage. Hope that wherever possible the use of AMR is the data can be alwaystransmitted in real time, used for customers and electric service providers in order to improve thequality of service and repair. The more rapid and accurate monitoring data sent will affect quality ofservice to customers that will reduce customer complaints.In fact, the level of SCADA system reliability can not be the ideal 100% without interference andcomplaint occurred. It could lead a disturbance complaint or grievance against the performance ofthe SCADA system. This will affect the level of reliability of distribution networks and generallymeasured by two parameters, namely: SAIDI (System Average Interruption Duration Index) andSAIFI (System Avarage Interuption Frequency Index). The higher the number SAIDI and SAIFIshows the level of reliability and service levels to customers getting worse. Based on statistics fromthe calculation of disturbances and complaints during three years experience decreasing of value isnumber of SAIDI = 0.69 and SAIFI = 0018, meaning that the level of service to the customerexperience improved or good.Key words: SCADA, SAIDI, SAIFI, Data and AMR